Analogous model approach for energy absorption capacity of superplasticised fibrous concrete under thermoshock - Elangovan, G. (Journal of Structural Engineering, 2024)
An analogous model based approach with 12 various relevant parameters ranging from properties of concrete ingredients, superplasticiser and fibres like steel, alkali resistant glass and polyester fibres for an impact test and compressive strength test under thermoshock have been developed and will be of great help to assess its strength before thermoshock, residual strength after thermoshock and also to the mix designer to estimate the properties of the fibrous concrete mixes even before they are prepared in the laboratory and thus save a lot of expensive experimentation. Sulphonated naphthalene based superplasticiser was used to reduce the cement content judiciously to make an economic concrete as well uniform dispersion of fibres and to serve our nation environmentally.